Rancang Bangun Lengan Robot Berbasis Arduino Nano - I Gede Purna Serineka; I Nyoman Piarsa; I Made Sunia Raharja (Jurnal Syntax Admiration, 2024)
Technological advances in the Industrial Revolution 4.0 era have had a big impact, especially in the industrial sector with the emergence of automatic robots which help increase efficiency and productivity. This research discusses the design of an Arduino Nano-based robot arm that is controlled using a joystick system. The objective of this research is to establish a robotic arm mechanical system that is responsive to the movement of the joystick and sevo motor as a driver of the closed feedback system and to identify the parameters for the success of the hard ware and software system in moving objects. The research stages used involve design analysis, device assembly, and system programming. The research results show that the developed robot arm is able to effectively move objects with success parameters including the type of shape and physical structure of the object being lifted. This research found that objects with simple shapes such as blocks have a higher level of ease of lifting, while soft physical structures also influence ease of lifting.